Identification and visualization of cellulase activities from Neurospora crassa - T. Mohammed; A. Radford (Fungal Genetics Reports, 1988)
To elucidate the nature of cellulase activities found in Neurospora crassa, we analyzed the "induced" spent culture medium for the components of the cellulase enzyme complex.